Analisis Analisis Kesulitan Mahasiswa/I Universitas Negeri Medan Dalam Memahami Materi Teorema Isomorfisma Grup: Solusi Efektif Meningkatkan Pemahaman Mata Kuliah Struktur Aljabar - SL Manurung; Juli Agina BR Surbakti; Andri Pratama Pencawan; Fazril Anshari (Departement of Mathematics Education, 2024)
This research aims to identify students' difficulties in understanding Group Isomorphism Theorem material and find effective solutions to improve understanding of this material. The background to this research is based on the observation that the Group Isomorphism Theorem is a complex concept in group theory, which often becomes an obstacle for students in achieving in-depth understanding. This research uses a descriptive qualitative approach with data collection methods through interviews and literature study. The data analysis technique used is descriptive statistical data analysis. The research results showed that students experienced several difficulties in understanding the Group Isomorphism Theorem material. These difficulties include: understanding how to prove the two theorems, understanding the symbols in the theorem, understanding the axioms used to determine whether a structure is a group or not, lack of understanding of the material as a whole, and the lack of references read. Several other common difficulties were also identified. To overcome these difficulties, this research proposes several effective solutions. These solutions include: the use of visual aids in learning, the use of concrete examples, the use of simple notation, the development of interactive teaching materials, the application of guidance and project-based learning, the use of appropriate references, and the application of continuous evaluation. The results of this research show that the level of difficulty in understanding Group Isomorphism Theorem material is still very high among students, but the proposed solutions can help improve their understanding significantly.